CONCEPTUALISE TOURISM SUPPORT SYSTEM THROUGH WEB-BASED GIS FOR COLLABORATIVE TOURISM PLANNING - Masron, Tarmiji; Marzuki, Azizan; Mohamed, Badaruddin; Mohd Ayob, Norizawati (PLANNING MALAYSIA, 2014)
Web based GIS plays a bigrole in tourism, especially in public and management use. The popularity of Web based GIS is increasing dramatically as seen through the number of web GIS emerging over the years. Web based GIS allows professionals, organizations and the public to share and collaborate on information unhindered by geographic boundaries. The integration of GIS with the World Wide Web (WWW) brought a new paradigm of enhancing the collaborative planning effort among stakeholders. It also became a new medium of inviting public participation in planning and management processes by providing information in the form of maps and data for public access and paving the path for data sharing with agencies having the same interest. This paper aims to explore the concept of web based GIS and identify how it can be used towards enhancing collaborative planning and public participation among tourism stakeholders and communities. The Langkawi Island Web GIS is a website which provides tourism related information about Langkawi Island and allows for public participation as an information supplier. Â 